Financial Resources, Corporate Governance, and Sustainability Performance: The Mediating Role of Financial Performance in Indonesian Manufacturing Firms - Fithri Suciati; Tri Widyastuti; Harnovinsah Harnovinsah; Darmansyah Darmansyah (Al-Qalam Institute, 2026)
This study investigates the relationships between financial resources, corporate governance, and corporate sustainability performance (CSP) in Indonesian manufacturing firms, with financial performance (FP) as a mediating mechanism. Although the Financial Services Authority’s (OJK) Sustainable Finance Roadmap encourages sustainability practices, sustainability disclosure among Indonesian firms remains inconsistent, and evidence regarding the role of internal financial resources in achieving CSP is inconclusive. Using a quantitative explanatory approach, this study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to 19 manufacturing firms listed on the Indonesia Stock Exchange with complete financial and sustainability reports during 2020–2024, resulting in 95 firm-year observations. The results show that corporate governance has a positive direct effect on CSP, whereas financial slack, financial capacity, and growth options exhibit significant negative direct effects. FP does not directly affect CSP but significantly mediates the relationship between financial resources and CSP, except for the governance–CSP relationship. These findings reveal a Financial Resource Sustainability Paradox, indicating that resource availability alone does not ensure sustainability commitment. This study contributes an integrated Financial Resource, Governance, and Sustainability framework and highlights the importance of governance mechanisms and effective financial resource conversion to improve sustainability outcomes.